Factors Influencing Consumer Buying Behavior in Uniqlo Retail Store - Merry C. N. Rumagit; Aarti Sharma; Antonette Angelle; Daisy Mui Hung Kee; Annie Ke Ching Nik; Azman bin Bachotan; Shiqi Bian; Christovel Pelealu (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2022)
The purposes of this study are to study the factors influencing consumers' purchasing behavior in Uniqlo, find determinants of consumers' purchasing behavior, and understand consumers' views on the various factors. The marketing idea is consumer-oriented, with a focus on the consumer rather than the product. We distributed a survey questionnaire to 100 Uniqlo consumers to collect data. The results show that consumers' purchasing behavior in Uniqlo is affected by psychological, personal, social, and cultural factors. The combination of these factors helps the consumer to make further purchasing decisions. Additional findings also provide specific features to improve Uniqlo's chances of enhancing customer satisfaction and suggestions for future development.